CRIMINAL LIABILITY FOR CRIMINAL OFFENDERS WHO DISTRIBUTE PHARMACEUTICAL PREPARATIONS THAT DO NOT MEET STANDARDS - Rasiman Ade Putra Rambe; -, Tamaulina Br. Sembiring; -, Siti Nurhayati; -, Yasmirah Mandasari Saragih (Journal of International Islamic Law, Human Right and Public Policy, 2024)
One of the implementation of health efforts as intended in Article 48 of Law Number 36 of 2009 concerning Health is carried out through security service activities, pharmaceutical preparations and medical devices. Pharmaceutical preparations in the form of drugs and medicinal ingredients must meet the requirements of the Indonesian pharmacopoeia or other standards. The aim of this research is to find out and analyze legal provisions regarding the quality and safety standards of pharmaceutical preparations in Indonesia, the factors that cause criminal acts of distributing pharmaceutical preparations that do not meet standards, and criminal liability for perpetrators of criminal acts of distributing pharmaceutical preparations that do not meet standards. standards. This type of research is normative juridical with library data collection methods (library research). The data sources used in this research are secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this research are: 1) Legal provisions for quality and safety standards for pharmaceutical preparations in Indonesia have been stated in Law Number 17 of 2023 concerning health. The legal provisions regulated in this Law include: a) Provisions for Distribution of Pharmaceutical Preparations (Drugs), b) Regulatory provisions regarding pharmaceutical preparations, and c) Sanctions for Criminal Actions for Distribution of Pharmaceutical Preparations (Drugs). 2) Factors that cause criminal acts of distributing pharmaceutical preparations that do not meet standards include: a) Financial gain, b) Lack of supervision and law enforcement, c) Economic Factors, d) Community Environmental Factors, and e) Business Actor Factors, 3) Criminal liability for criminals who distribute pharmaceutical preparations that do not meet standards emphasizes the principles of legality in criminal law, where a person can only be punished if they are proven to have made a mistake.